Peningkatan Pemahaman Kerukunan Umat Beragama Melalui Sistem Halaqah - Nur Kharomah, Larasati; Rismayanti, Rismayanti; Hariyati, Jamiah; Hajatina, Hajatina; Umami, Nurliza; Rozali, M (MEUSEURAYA - Jurnal Pengabdian Masyarakat, 2024)
Community service activities using the halaqah system aim to socialize the values of religious harmony through non-formal education in communities using the halaqah system. The problem identified is that there is still discrimination between religious communities in Litur Village area, which can hinder harmonious social life. Activities carried out include counseling, group discussions and workshops involving religious leaders, community leaders and youth. The expected result is increased public understanding and awareness of the importance of religious harmony, as well as the establishment of more harmonious relations between religious communities in the region.